The conflictive discourse of density in London's planning system - Matillana, Fabrizio; Livingstone, Nicola (Frontiers in Sustainable Cities, 2023)
Density in planning presents a series of conflicts in its use based on how it is defined and perceived. When codified into planning policy, however, it is conflictive due to how it manages strategic and local planning needs and the subjective experiences of density. This article researches the evolution of density policy in London, from the density matrix to the current design-led approach, examining how this conflictive discourse manifests and is resolved within planning practice. Extensive research of planning applications referred to the Mayor of London, known as called-in applications, examine the strategic and local conflicts in a design-led approach. To further inquire on the findings of the extensive research, semi-structured interviews were conducted to design officers across London local authorities to collect their experiences on the practice of density policies and the design-led approach in development management. The results of the planning application research show a tension between design-led approach and a strategic dominance to deliver more housing in London. The design officer interview explains further how this emerges in negotiations and signal into potential solutions. The article presents the deficiencies in density policy and proposes design-led tools to address the limitations of the current approach.